Emerging Trends in Marketing in India: A Study on Retailers: Exploring the Shift towards Digital Marketing in the Indian Retail Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Digital marketing is really important for the human use of knowledge exchange in this new age. In order to promote goods or labels digital marketing is the type of interactive advertising that is available to the customer. It is made up of online marketing, email marketing or web marketing. Banner ads, search engine optimize (SEO) and pay per click are now part of the digital marketing scenario. In digital marketing, e-mail, RSS, voice, fax, tweeting, podcasting, video feeds, wireless text, and immediate messages are all included. There is a broad spectrum of digital marketing. It is the method of electronic data communication in order to turn consumer products and services digitally into the marketplace. Emerging trend industries around the world are moving towards digital marketing. The digital marketing objective is attractive to customers and enables the consumers to interfere with the commodity by high-quality digital media. Today, smartphone users are higher than last year. Sales are quite difficult to boost. Changes in the processing of website messages and website ads will offer the sales staff a huge boost. Digital marketing software innovation is more used because disruption is out of the picture without digital marketing. Opportunities and forecasts are prosperous. There is some online marketing for the Amazon, the flipchart, the eBay business, the club factory, etc. There are 450 million internet users in India, the latest report reports.